2008
DOI: 10.4049/jimmunol.181.6.4080
|View full text |Cite
|
Sign up to set email alerts
|

Inside-Out Regulation of FcαRI (CD89) Depends on PP2A

Abstract: To achieve a correct cellular immune response toward pathogens, interaction between FcR and their ligands must be regulated. The Fc receptor for IgA, FcαRI, is pivotal for the inflammatory responses against IgA-opsonized pathogens. Cytokine-induced inside-out signaling through the intracellular FcαRI tail is important for FcαRI-IgA binding. However, the underlying molecular mechanism governing this process is not well understood. In this study, we report that PP2A can act as a molecular switch in FcαRI activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 48 publications
1
37
0
Order By: Relevance
“…17 Unlike Fc␣RI, however, serine phosphorylation of the cytosolic tail of Fc␥RI ␣-chain is unlikely to play a role during inside-out regulation, because a truncated receptor lacking all serines was found to respond to cytokine stimulation (data not shown). Strikingly, PI-3K inhibition did not affect cytokine-enhanced IC binding to Fc␥R,I suggesting distinct mechanisms underlying Fc␥RI regulation compared with Fc␣RI.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…17 Unlike Fc␣RI, however, serine phosphorylation of the cytosolic tail of Fc␥RI ␣-chain is unlikely to play a role during inside-out regulation, because a truncated receptor lacking all serines was found to respond to cytokine stimulation (data not shown). Strikingly, PI-3K inhibition did not affect cytokine-enhanced IC binding to Fc␥R,I suggesting distinct mechanisms underlying Fc␥RI regulation compared with Fc␣RI.…”
Section: Discussionmentioning
confidence: 96%
“…It has been shown that Fc␣RI inside-out regulation in Ba/F3 cells is dependent on PI-3K and protein phosphatase 2 (PP2a). 17,18 We investigated whether similar signaling pathways underlie Fc␥RI inside-out regulation. In our model, both a PI3-Kinase inhibitor (LY294002) 32 and a MEK1/2 inhibitor (U0126) 33 did not affect IL-3-enhanced binding to mIgG2a-IC ( Figure 4A).…”
Section: Cytokine Stimulation Enhances Fc␥ri Binding To Opsonized Tummentioning
confidence: 99%
See 1 more Smart Citation
“…This observation might be related to Fc␣RI splice variants differently expressed by human leukocytes (36,37) and upon cellular activation (38). Furthermore, the functionality of Fc␣RI is dependent on the interaction with the FcR␥ chain and sensitive to inside-out signaling (39,40). Thus, the (1) antibodies as well as 225-IgG1 induced similar specific lysis in macrophage-mediated ADCC assays of A431 tumor cells.…”
Section: Advantages and Disadvantages Of Iga Iso-and Allotypementioning
confidence: 94%
“…Our previous finding that the C2 domains play little or no role in the kinetics of IgY binding to receptor (6), unlike the homologous C⑀2 domains in IgE (30) (29). Dephosphorylation of Fc␣RI by protein phosphatase 2A has now been identified as the activation switch for IgA bound to its receptor on neutrophils (31). A mutant IgG, binding only one molecule of FcRn, the fetal and IgG homeostasis receptor (32), has been used to show that 1:1 receptor:antibody stoichiometry does decrease the efficiency of transcytosis and recycling and also does increase the proportion of antibody targeted for degradation (33).…”
mentioning
confidence: 99%